Afectación a la progresividad laboral, por la regla de solución de continuidad en los contratos de prestación de servicios. (2023)
On September 9, 2021, the Consejo de Estado Colombiano (CE) with sentence SUJ025-CE-S2-2021, establishes a jurisprudential sub-rule, determining the continuity solution at 30 business days, between the existence of a contract and the execution of the following. From the analysis it can be deduced that the establishment of this jurisprudence by the EC violates the principle of labor progressivity.